Occupational experiences and brain health outcomes in older age - Jiao, Yuqin, author; Burzynska, Aga Z., advisor; Fisher, Gwen G., committee member; Bielak, Allison A., committee member (Colorado State University. Libraries, 2019)
Most adults spend half of their awake time at work. Although greater midlife work complexity has been consistently linked to better cognitive outcomes in older age, little is known about how occupational experiences associate with brain aging. Two studies have found an association between midlife managerial experience and slower hippocampal atrophy in older adults with no (Suo et al., 2012) and mild cognitive impairment (Suo et al, 2016). However, no study has considered to include both protective (enriching) and risk (stress-related) occupational factors in relation to neurocognitive health in aging, which we recently conceptualized as the BOSS model (Brain aging: Occupational Stimulation and Stress; Burzynska, Jiao, Ganster, 2018). To empirically test this model, we assessed five stimulating and stress occupational constructs to reflect the characteristics of most recent main occupations in 101 cognitively healthy older adults (mean age=70, a subsample of "Fit & Active Seniors Trial (FAST)" trial, clinical study identifier NCT01472744). To obtain the above constructs, we did a priori grouping then factor analysis on 86 items from three well-established occupational experience questionnaires (Spector & Jex, 1998; Morgeson & Humphrey, 2006). We measured hippocampal volume with Magnetic Resonance Imaging and cognitive tasks with Virginia Cognitive Battery and spatial working memory tasks. Greater physical demands at work were associated with smaller bilateral hippocampi and lower performance on spatial working memory tasks, independent of the effects of age, education, estimated total intracranial volume, sensor-measured lifestyle moderate-to-vigorous physical activity, and current employment status. We found no evidence for greater hippocampal volume or better cognition as a function of more stimulating occupational exposures. These findings have furthered our understanding of the neurocognitive correlates of physical demands in healthy older adults and also have highlighted the importance of using longitudinal measures in future studies to decipher the underlying neural mechanisms of occupational exposures.
Zip file contains supplementary tables.